Physical Evaluation of Transfersome that Contains Pandan Leaves Extract (Pandanus amaryllifolius R.) - Rini Ambarwati; Yulianita Yulianita (Journal of Tropical Pharmacy and Chemistry, 2021)
Pandan leaves have been researched and have effectiveness in the treatment of burns. The process of healing burns takes a long time and cause a hard tissue because it loses its elasticity, making it difficult to penetrate. In this study, pandanus leaves were formulated into the nanovesicle carrier system, namely trasfersom. Transfersomes have the ability to deform, namely the ability to reduce the particle size 5-10 times from the original size when passing through the gaps between cells so that transfersom can increase the penetration of active substances. The three formulas used are based on the ratio of concentrations of trasfersome vesicles, namely phospholipids and span 80. Formula 1 is (90:10), Formula 2 (85:15) and Formula 3 (80:20). The best formula is determined based on transfersom characterization, including particle size and PDI (solidispersity index), zeta potential, entrapment efficiency, deformability, and TEM particle morphology. The results showed that Formula 3 (80:20) is the most stable formula with an average particle size of 730.1 ± 4.9 nm, PDI value <0.7, zeta potential - 9.94 ± 1.02 mV, efficiency absorption 80.23%, and the deformability value 6.225.